Improvement of mechanical properties of chitosan-based films via physical treatment of film-forming solution - Wasina Thakhiew (2018)
© 2015 Elsevier Ltd. All rights reserved. Although biopolymer films are of interest from many points of view, these films have inferior mechanical properties to commercially available synthetic polymer films. The present study therefore aimed to seek a means to improve the mechanical properties of biopolymer films; chitosan was chosen as the biopolymer of interest. The effects of selected physical methods that can be incorporated into the film-forming solution preparation process were investigated. Heat treatment by heating the film-forming solution at 70 °C for 1 h to induce thermal cross-linkage of chitosan polymer chains was evaluated. In addition, the effects of some processes that led to the homogenization of the chitosan solution and plasticizer (glycerol) were tested. These included rotor-stator homogenization at 9600 rpm at atmospheric pressure and two-stage high-pressure homogenization at a gauge pressure of either 10/5, 20/5 or 30/5 MPa. The prepared film-forming solutions were then dried by hot air drying at 40 °C and the obtained films were tested for their properties and characteristics in terms of the tensile strength, percent elongation, X-ray diffraction as well as dynamic mechanical analysis patterns. Chitosan film exhibiting the best mechanical properties was the one prepared from the film solution that did not pass through the heat treatment but passed through the high-pressure homogenization at 10/5 MPa, with the tensile strength and percent elongation of about 46 MPa and 36%, respectively. Compared to the control film, there was an increase of about 23% in the tensile strength and 25% in the percent elongation.